HISTORIC BUILDING APPLICATIONS WITH IN JAKARTA USING MACROMEDIA FLASH 8.0 - Adly Hilman Maris; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Scientific writing is about an application that Historic Buildings in Jakarta. This application was created to help users who want to know information about the development history of the museum with an attractive appearance and interactive and implement information technology that is being developed at this time. In scientific writing, the author makes an application using Macromedia Flash 8.0 ActionScript 2.0 programming language for facilitate the author in pembutan application that displays text, Motion picture and sound. thus can be expected to attract more users in identifying the existing historic buildings in jakarta.